2020
DOI: 10.1001/jamaoncol.2019.4794
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Early Breast Cancer With a High 21-Gene Recurrence Score of 26 to 100 Assigned to Adjuvant Chemotherapy Plus Endocrine Therapy

Abstract: IMPORTANCE A high 21-gene recurrence score (RS) by breast cancer assay is prognostic for distant recurrence of early breast cancer after local therapy and endocrine therapy alone, and for chemotherapy benefit. OBJECTIVE To describe clinical outcomes for women with a high RS who received adjuvant chemotherapy plus endocrine therapy in the TAILORx trial, a population expected to have a high distant recurrence rate with endocrine therapy alone. DESIGN, SETTING, AND PARTICIPANTS In this secondary analysis of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 13 publications
5
128
0
1
Order By: Relevance
“…Given these findings, the 21-gene RS assay has already had a significant impact on treatment decisions [14][15][16], overall use of chemotherapy [16][17][18], and survival of patients [19]. For patients with an intermediate RS, results from the recent prospective Trial Assigning Individualized Options for Treatment (TAILORx) trial [20], which was designed to test whether chemotherapy is beneficial for patients with hormone receptor-positive, HER2 (human epidermal growth factor receptor 2)-negative, node-negative BC who had a mid-range 21-gene RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), new intermediate score), revealed that adjuvant endocrine therapy alone was non-inferior to chemo-endocrine therapy in the analysis of invasive disease-free survival (IDFS). Results from a subgroup analysis suggested that chemotherapy may be of some benefit for patients 50 years of age or younger with an RS of 16-25.…”
Section: Introductionmentioning
confidence: 99%
“…Given these findings, the 21-gene RS assay has already had a significant impact on treatment decisions [14][15][16], overall use of chemotherapy [16][17][18], and survival of patients [19]. For patients with an intermediate RS, results from the recent prospective Trial Assigning Individualized Options for Treatment (TAILORx) trial [20], which was designed to test whether chemotherapy is beneficial for patients with hormone receptor-positive, HER2 (human epidermal growth factor receptor 2)-negative, node-negative BC who had a mid-range 21-gene RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), new intermediate score), revealed that adjuvant endocrine therapy alone was non-inferior to chemo-endocrine therapy in the analysis of invasive disease-free survival (IDFS). Results from a subgroup analysis suggested that chemotherapy may be of some benefit for patients 50 years of age or younger with an RS of 16-25.…”
Section: Introductionmentioning
confidence: 99%
“…In a secondary analysis of the TAILORx trial, 1389 patients with HR+, HER2-, N0 breast cancer who had a high RS of 26 or more were identi ed and 89 of the patients had no chemotherapy [27]. The study reported that patients without chemotherapy had a worse prognosis in invasive disease-free survival (IDFS) than patients with chemotherapy (HR with 95% CI: 0.48, 0.29-0.80), rather than freedom from recurrence at a distant site (HR with 95% CI: 0.74, 0.32-1.69).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we set RS > 25 as the objective of prediction because this was used for de ning high-risk RS in the prospective TAILORx trial. We postulate that the chemotherapy should be included in treatment for patients with an RS of 26-30 since in the TAILORx trial those patients were assigned to use chemotherapy and had better clinical results than expected outcomes with endocrine monotherapy (18). Moreover, we only included patients > 50 years, because in patients of 50 years of age or younger some chemotherapy bene t could be found in those had an RS of 16-25 (6).…”
Section: Discussionmentioning
confidence: 99%